Neutralization of multiply charged ground-state ions by collective electron transfer from an environment - Marder, Lutz; Küstner-Wetekam, Catmarna; Kiefer, Nils; Viehmann, Johannes; Golchert, Niklas; Heikura, Emilia; Trinter, Florian; Cubaynes, Denis; Palaudoux, Jérôme; Penent, Francis; Ehresmann, Arno; Cederbaum, Lorenz S.; et al. (Physical review letters, 2025)
Highly charged cations are omnipresent species after the interaction of high-energy or high-intensity light with matter. When embedded in environments, the mechanism and outcome of the redistribution of the cation’s charge are crucial for the further fate of the whole system. Generally, ground-state cations can decay by charge transfer, proceeding radiatively, through nuclear dynamics, or by electron-transfer-mediated decay (ETMD). ETMD causes electron emission from a remote neighbor and appears ubiquitous in loosely bound systems. It remained unclear how multiply charged ions decay if conventional ETMD channels are closed. Here, we show that a yet undiscovered variant of ETMD is possible, where multiple electrons are collectively transferred. Explicitly, we observe ETMD in which two electrons from two distinct neighbors (partially) neutralize a multiply charged ion, and an electron from a fourth site is emitted. According to the established nomenclature, we suggest naming the process ETMD(4).